The artists and staff of Tobwabba Art. - Tobwabba Art. ([Forster, N.S.W.] : Tobwabba Art, 1997)
Gives brief profiles of the 18 artists in the group, and examples of their work.
Keywords: Art, Aboriginal Australian; Artists, Aboriginal Australian; Art - Artists; Forster / Tuncurry (NSW N Coast SI56-02)